Resection of ruptured aneurysm associated with bilateral anomalous posterior inferior cerebellar anastomotic arteries: case report and review of literature - Han, Qingdong; Wang, Zongqi; Liu, Tong; Huang, Yabo (Frontiers in Neurology, 2023)
Introduction: Aneurysms on posterior inferior cerebellar artery (PICA)may be not the major part as to intracranial aneurysm. Especially, aneurysm located on the bilateral posterior inferior cerebellar anastomotic artery has abnormally anatomical characteristics in vessel wall and then causes stroke including subarachnoid hemorrhage. This case report explores the direct resection of ruptured aneurysm associated with bilateral anomalous anastomotic artery of PICA. Methods: The authors shown a 53-year-old woman suffering sudden severe headache and vomiting for more than 3 hours and was admitted to our hospital. Emergency computed tomography (CT) revealed subarachnoid hemorrhage (SAH) in the third and fourth ventricles. Pre-operative 3 Dimensions-digital subtraction angiography (3-D DSA) indicated a ruptured aneurysm located on the bilateral posterior inferior cerebellar anastomotic artery. Postoperative pathological findings indicated the characteristics of parent artery PICA and control aneurysm. The authors performed an overview of PICA aneurysm with anomalous variation in the Pubmed, web of science and Medline database. The search was until August 1, 2023.Related terms “posterior inferior cerebellar artery” And” aneurysm” AND “anatomical variants” were used to search the review. The reasons for anomalous variation anastomosis between bilateral PICAs were analyzed. Results: The aneurysm was resected successfully. Post-operative 3-D DSA revealed the disappearance of the aneurysm. The vessel wall of anastomotic PICA shown that neovascularized hyperplasia, abnormal arrangement of smooth muscle, CD31+ endothelial cells and SMA+ smooth muscle cells. In contrast, when it comes to aneurysm, the wall at the location of fracture thinned, and the local nodular protrusion and CD31+ endothelial cells existed. No neurological deficits were found at her 1-year follow-up visit (mRS score of 0). Conclusions: Direct resection of ruptured aneurysm associated with bilateral anomalous posterior inferior cerebellar anastomotic arteries was effective treatment and careful consideration of the anatomical characteristics concerning the interesting aneurysm and the variant PICA was critical for sate treatment. Also, literatures as to the lesion were reviewed.